Correlation between Cepheid GeneXpert and Abbott M2000 assays for HIV viral load measurements. (April 2020) - Manavi, Kaveh; Hodson, James; Masuka, Sindiso; Singo, Mebie; Dedicoat, Katie; Osman, Husam
Measurement of HIV viral load (VL) is the best indicator of success of antiretroviral therapy. We investigated the correlation between results by the Cepheid GeneXpert and a standard of care VL assay (Abbott M2000). This was a prospective study of people living with HIV who attended the department for routine VL measurement with the Abbott M2000. Consenting patients agreed to provide one extra blood sample for VL measurement with the Cepheid GeneXpert assay. One hundred patients consented to participate in the study. There were 18 patients with VL ≥ 40 copies/mL and 75 patients with VL < 40 copies on both assays. The two assays had 93% agreement, with a kappa of 0.79 ( p < 0.001). Treating VL as a continuous variable found measurements to be significantly higher on the Cepheid GeneXpert assay than the Abbott ( p = 0.002). Analysis of samples with VL ≥ 40 copies/mL on either assay ( n = 25) found the mean difference between the two assays to be 0.31 log10 copies/mL (95% limits of agreement: −0.63, 1.25). Whilst the measurements on the two assays are relatively highly correlated, there is a clear bias, with the Cepheid GeneXpert tending to give higher VL values.